2011
DOI: 10.1111/j.1742-481x.2011.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated uric acid correlates with wound severity

Abstract: Chronic venous leg ulcers are a major health issue and represent an often overlooked area of biomedical research. Nevertheless, it is becoming increasingly evident that new approaches to enhance healing outcomes may arise through better understanding the processes involved in the formation of chronic wounds. We have for the first time shown that the terminal purine catabolite uric acid (UA) is elevated in wound fluid (WF) from chronic venous leg ulcers with relative concentrations correlating with wound chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 45 publications
3
66
0
Order By: Relevance
“…Such inflammatory mediators play significant roles in inflammatory responses (Rider & Jordan, ; Zhao, Liang, Clarke, Jackson, & Xue, ). Furthermore, a study of 29 patients with CLUs by Fernandez, Upton, Edwards, Finlayson, and Shooter () found an increase in the level of uric acid in wound fluid was associated with increased severity of chronic venous leg ulcers (Fernandez et al, ; Fernandez, Upton, & Shooter, ). Thus, the current finding somewhat supports suggested links found in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Such inflammatory mediators play significant roles in inflammatory responses (Rider & Jordan, ; Zhao, Liang, Clarke, Jackson, & Xue, ). Furthermore, a study of 29 patients with CLUs by Fernandez, Upton, Edwards, Finlayson, and Shooter () found an increase in the level of uric acid in wound fluid was associated with increased severity of chronic venous leg ulcers (Fernandez et al, ; Fernandez, Upton, & Shooter, ). Thus, the current finding somewhat supports suggested links found in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…The electroanalytical performance of these fi lms has been shown to accurately measure pH, having been tested in simulated and whole blood samples. [ 18,19 ] Thus far, urate has been used as an indicator of pH yet it has been established in recent years that its quantifi cation is of considerable interest as Fernandez et al (2012) have shown that its concentration is elevated as a consequence of tissue remodeling within the wound. The cellular trauma and associated healing processes result in the release of adenosine triphosphate (ATP) into the extracellular wound matrix, which is subsequently metabolized into uric acid.…”
Section: Research Newsmentioning
confidence: 99%
“…The cellular trauma and associated healing processes result in the release of adenosine triphosphate (ATP) into the extracellular wound matrix, which is subsequently metabolized into uric acid. [ 24 ] Thus, the ability to electrochemically monitor its concentration could be useful in determining the extent of infl ammation and the subsequent response to treatment -therein providing insights into the healing process. [ 24 ] This can be achieved through a procedurally simpler approach, involving the amperometric oxidation measurement of uric acid, As a biomarker, it has the advantage of being found in relatively high concentrations and there is an extensive amount of literature on its electrochemical detection.…”
Section: Research Newsmentioning
confidence: 99%
See 2 more Smart Citations